Angiogenesis in Tissue Engineering: As Nature Intended? - Mastrullo, Valeria; Cathery, William; Velliou, Eirini; Madeddu, Paolo; Campagnolo, Paola (Frontiers in Bioengineering and Biotechnology, 2020)
Despite the steady increase in the number of studies focusing on the development of tissue engineered constructs, the solutions delivered to the clinic are still limited. In particular, the lack of mature and functional vasculature, greatly limits the size and complexity of the scaffolds. If tissue engineering aims at replacing large portions of tissue in order to repair significant defects, a more thorough understanding of the mechanisms and the players regulating the angiogenic process is required in the field. This review will present the current biological understanding and technological advancements addressing the imperfect formation of mature blood vessels within tissue engineered structures